2001
DOI: 10.1179/136217101101538884
|View full text |Cite
|
Sign up to set email alerts
|

Coupled thermomechanical analysis of friction stir welding process using simplified models

Abstract: It is widely recognised that the fundamental mechanisms associated with the weld formation process and their relationships with welding parameters are complex and remain to be fully understood. The present paper reports a series of general findings based on a set of simplified numerical models that were designed to elucidate various aspects of the complex thermomechanical phenomena associated with friction stir welding. The following phenomena were investigated in separate numerical models: (i) coupled frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 2 publications
0
66
0
2
Order By: Relevance
“…Generally this state is reached before strain drops to a low value, ǫ = 1, and since the strains involved in FSW are much larger, it may be assumed that a single set of material constants corresponding to steady-state deformation can be utilised with the assumption that they are independent of strain. Most of the recent studies have considered the temperature dependent thermal conductivity, specific heat and yield stress for the work-piece [39][40][41][65][66][67]. The tool material commonly used for the FSW of aluminium alloys, steels and Ti-6Al-4V are tool steel and tungsten, respectively.…”
Section: Principles Of Heat Transfer and Materials Flowmentioning
confidence: 99%
“…Generally this state is reached before strain drops to a low value, ǫ = 1, and since the strains involved in FSW are much larger, it may be assumed that a single set of material constants corresponding to steady-state deformation can be utilised with the assumption that they are independent of strain. Most of the recent studies have considered the temperature dependent thermal conductivity, specific heat and yield stress for the work-piece [39][40][41][65][66][67]. The tool material commonly used for the FSW of aluminium alloys, steels and Ti-6Al-4V are tool steel and tungsten, respectively.…”
Section: Principles Of Heat Transfer and Materials Flowmentioning
confidence: 99%
“…In the model, a transient thermal condition in which the power was recorded experimentally and defined in the model as a constant value was used. Dong et al [84] and Chao et al [85] compared the experimental and the numerical results of the generated heat energy during FSW using the Lagrangian method. In Chao's model, a steady state condition was employed for the tool and a transient condition was used for the plates.…”
Section: Lagrangian Eulerian Methodsmentioning
confidence: 99%
“…Dong et al developed a work [6] in which they reported a series of general findings based on a set of simplified numerical models that were designed to elucidate various aspects of the complex thermomechanical phenomena associated with FSW. A friction-induced heat generation model was used to quantify the contributions of coupled thermomechanical friction heating, including nonlinear interfacial phenomena between the tooling (e.g., stir pin) and material being welded.…”
Section: Introductionmentioning
confidence: 99%